(untitled) (Homoeopathy for All, 2025)
Bach flower remedies are commonly used in Homoeopathy and they both work on the principle of dilution or the lesser is always better. Both stimulate our body to fight the disease rather than fighting against the disease. Dr. Bach believed that one is prone to sickness when he is mentally unfit or ill. Hence, these medicines derived from plant sources improves the mood and help the patient heal from the disease. However, very few quality trials have been conducted on Bach flower remedies with lack of standardization, hence, more studies are suggested and encouraged and a regulatory body for standardization.